2006
DOI: 10.1007/s00018-006-6007-9
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles: novel regulators of cell function; evolutionary aspects

Abstract: Identification of rate-limiting steps or components of intracellular second messenger systems holds promise to effectively interfere with these pathways under pathological conditions. The emerging literature on a recently identified family of signalling regulator proteins, called tribbles gives interesting clues for how these proteins seem to link several 'independent' signal processing systems together. Via their unique way of action, tribbles co-ordinate the activation and suppression of the various interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Using a literature gene-set comparison approach for late graft injury, we identified TRIB1, a human homolog of Drosophila tribbles, [15][16][17] as a potentially informative biomarker. TRIB1 is a scarcely characterized member of the tribbles family (see references 22,23 for review) that has been shown to be a potent regulator of cell signaling 18 in various cells lines. We thus explored the potential of TRIB1 as a tissue, peripheral blood, and urine biomarker by measuring its mRNA profiles in graft biopsies, blood, and urine from healthy volunteers and kidney transplant recipients with different histologic and/or clinical diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a literature gene-set comparison approach for late graft injury, we identified TRIB1, a human homolog of Drosophila tribbles, [15][16][17] as a potentially informative biomarker. TRIB1 is a scarcely characterized member of the tribbles family (see references 22,23 for review) that has been shown to be a potent regulator of cell signaling 18 in various cells lines. We thus explored the potential of TRIB1 as a tissue, peripheral blood, and urine biomarker by measuring its mRNA profiles in graft biopsies, blood, and urine from healthy volunteers and kidney transplant recipients with different histologic and/or clinical diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this study was presented as an abstract at the World Transplant Congress (Boston, MA; July [22][23][24][25][26][27] 2006) and at the American Transplant Congress (San Francisco, CA; May 5-9, 2007).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In contrast, the Trib domain includes a degenerate LRD motif (HRD) in the potential catalytic site but completely lacks the VAIK and DFG domains (Hegedus et al, 2006; Fig. 2B).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…TRIB1 is located on chromosome 8q24 and regulates mitogen-activated protein kinase (MAPK) as a presumed adaptor or scaffolding protein (Kiss-Toth et al 2004;Hegedus et al 2006). TRIB1 regulates vascular smooth muscle cell proliferation and chemotaxis via the Jun kinase pathway and is selectively overexpressed in chronically inflamed human atherosclerotic arteries, which suggests that TRIB1 may play an important role in the atherosclerotic process (Sung et al 2007).…”
Section: Introductionmentioning
confidence: 99%